The Reflection of the Idiom in the Poetic Language by the poet Wali Diwana (Raparin Journal of Humanities (RJH), 2024)
Generally, Idiomatic expressions are characterized by great importance in creative texts and poetic texts in particular, because they have special connotations that express the extent of the poet's creative ability since the poets embody the content of their poems implicitly within the texts, in an attempt to increase the artistic taste of the reader.This study is entitled “The Reflection of the Idiom in the Poetic Language by the  poet Wali Diwana”. We took the poems of the aforementioned poet as a sample for the poets of his time. In those days, the poets of southern Kurdistan, in general, implicitly expressed the living style and social conditions in their poems.The idiomatic expressions of all kinds were embodied in the poems of the above-mentioned poet, in a special style and technique, and this was reflected in the contents of his poems.The importance of this study turns out to be an applied study, and on the other hand, it opens the way for other researchers in the literary and linguistic fields to raise this issue in their studies.